According to the Book - Valverde, Gilbert A. author. aut Link
IX, 199 p.
Keywords: How are curriculum policies translated into opportunities to learn in the classroom? According to the Book presents findings from the largest cross-national study of textbooks carried out to date - the curriculum analysis of the 1995 Third International Mathematics and Science Study (TIMSS). This study included a detailed, page-by-page, inventory of the mathematics and science content, pedagogy, and other characteristics collected from hundreds of textbooks in over forty countries. Drawing on these data, the authors investigate the rhetorical and pedagogical features of textbooks to understand how they promote and constrain educational opportunities. They investigate how textbooks are constructed and how they structure diverse elements into prescriptions for teaching practice. The authors break new ground in understanding textbooks in terms of different educational opportunities that they make possible. The book examines policy implications from these new understandings. In particular, conclusions are offered regarding the role of textbooks in curriculum-driven educational reform, in light of their role as promoters of qualitatively distinct educational opportunities.